Photocatalytic Degradation of Textile Orange 16 Reactive Dye by ZnO Nanoparticles Synthesized via Green Route Using Punica Granatum Leaf Extract - Salma A. Al-Zahrani; Mallikarjunagouda B. Patil; Shridhar N. Mathad; Arun Y. Patil; Ahmed A. Otaibi; Najat Masood; Dorsaf Mansour; Anish Khan; A. Manikandan; Edi Syafri (Crystals, 2023)
Since it does not use any dangerous chemicals and is a simple, low-cost process, the green synthesis approach for nanoparticle creation has several benefits compared to the physical and chemical synthesis routes. The current study describes an environmentally friendly synthesis of zinc oxide (ZnO) nanoparticles (NPs) using an extract of Punica granatum plant leaves. Fourier-transform infrared spectroscopy (FTIR), ultraviolet-visible spectrophotometer (UV-Vis), field-emission scanning electron microscopy (FESEM), energy-dispersive X-ray spectroscopy, and X-ray diffraction techniques were used to characterize the morphology, composition, and structural properties of the synthesized zinc oxide nanoparticles. The XRD pattern reveals that the ZnO nanoparticles are crystalline and have a diameter of 20 nm. According to the FESEM studies, the ZnO-NPs have sizes ranging from 50 to 100 nm on average and are almost spherical. When exposed to direct sunlight, the produced ZnO-NPs demonstrate impressive photocatalytic oxidation of textile Orange 16, a reactive dye. As a result, our research advances the development of a green photocatalyst for the removal of harmful dyes from water.